Effects of combined treatment with ochratoxin A and citrinin on oxidative damage in kidneys and liver of rats. (May 2018) - Rašić, Dubravka; Mladinić, Marin; Želježić, Davor; Pizent, Alica; Stefanović, Srđan; Milićević, Dragan; Konjevoda, Paško; Peraica, Maja
Abstract: A multimycotoxin analysis approach in grains results in frequent simultaneous findings of nephrotoxic mycotoxins ochratoxin A (OTA) and citrinin (CTN). The mechanism of CTN and OTA toxicities in biological systems is not fully understood but it is known that oxidative stress is involved. In this study, oxidative damage of DNA, lipids, and the concentration of glutathione (GSH), as well as possible antioxidative effects of resveratrol (RSV) were studied in vivo . Male adult Wistar rats were treated orally with OTA (0.125 and 0.250 mg kg −1  b.w.), RSV (20 mg kg −1  b.w.) for 21 days, CTN (20 mg kg −1  b.w.) for two days or with their combinations. The hOGG1 modified comet assay revealed kidneys and liver oxidative DNA damage in OTA + CTN treated animals, which was not reversed by RSV. CTN did not reduce glutathione (GSH) or increase malondialdehyde (MDA) concentration in any tissue, while OTA reduced kidneys GSH and increased kidneys and liver MDA. RSV increased GSH concentrations in all tissues and decreased MDA concentration in the liver only. Oxidative stress is involved in the toxicity of OTA and CTN but it seems that it differs significantly in organs. Most of the effects on GSH and MDA in combined toxicity may be attributed to the toxic effects of OTA. RSV was effective in restoring the depleted GSH in all tissues but had no effect on the MDA concentration and DNA damage. Highlights: Combined effects of ochratoxin A and citrinin were studied on male Wistar rats. The oxidative stress parameters were measured in kidneys, liver and plasma. It was confirmed that oxidative stress is involved in ochratoxin A and citrinin toxicity. Involvement of oxidative stress in the mechanism of their combined toxicity differs significantly by organ. RSV was effective in restoring depleted GSH in all tissues but had no effect on MDA concentration or DNA damage.